Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1097/gco.0b013e32807fb199
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes after in-vitro fertilization

Abstract: Some prospective observational studies compare maternal and perinatal outcomes in in-vitro fertilization pregnancies. Larger studies show that adverse pregnancy outcomes such as preeclampsia, gestational hypertension, placental abruption, placenta praevia, and preterm delivery increase significantly with in-vitro fertilization. Perinatal adverse outcomes such as prematurity and those related to plurality of the pregnancy also increase. All patients undergoing in-vitro fertilization should have careful counsell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 53 publications
2
30
1
1
Order By: Relevance
“…In a systematic review [21], Shevell et al [3] found that increased maternal complications such as 6 fold high increased placenta previa, 1.6 fold high gestational hypertension, 0.5 fold higher gestational diabetes, 2.4 fold high placental abruption, 2 fold higher caesarean delivery rates. Kallen et al [22] and Romundstad et al [23] found increased placenta previa rates in IVF cycles than naturally conceived pregnancies, 4 fold and 6 fold higher respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review [21], Shevell et al [3] found that increased maternal complications such as 6 fold high increased placenta previa, 1.6 fold high gestational hypertension, 0.5 fold higher gestational diabetes, 2.4 fold high placental abruption, 2 fold higher caesarean delivery rates. Kallen et al [22] and Romundstad et al [23] found increased placenta previa rates in IVF cycles than naturally conceived pregnancies, 4 fold and 6 fold higher respectively.…”
Section: Discussionmentioning
confidence: 99%
“…First, because we included only singleton births, our findings may not be applicable to multi-fetal pregnancies, whose maternal and perinatal risk factors and outcomes can differ from those of singleton pregnancies. 25 All of the maternal variables we found to be associated with maternal and neonatal ICU admission, except for hospital admission in the preceding year, were captured in the index hospital admission. Hence, the effects of pre-existing maternal comorbidities could not be distinguished from those arising at the time of, or soon after, ICU admission.…”
Section: Strengths and Limitationsmentioning
confidence: 94%
“…are linked with the couple's underlying infertility factors, medical factors, maternal age, obesity or the ART processes themselves (Mukhopadhaya & Arulkumaran, 2007). For example, Chen et al (2009) in their retrospective Canadian study found that pre-eclampsia occurred more frequently in women who had conceived through IVF than in women who had conceived through two other ARTs: ovulation induction or intrauterine insemination.…”
mentioning
confidence: 99%
“…Furthermore, a two fold increase in gestational diabetes mellitus is seen in women undergoing ART, which may be associated with the underlying cause of infertility, e.g. polycystic ovarian syndrome (Mukhopadhaya & Arulkumaran, 2007).…”
mentioning
confidence: 99%